White fingers, cold environment, and vibration - exposure among Swedish construction workers - Lage Burström; Bengt Järvholm; Tohr Nilsson; Jens Wahlström (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVES: The aim of this study was to examine the association between white fingers, cold environment, and exposure to hand-arm vibration (HAV). The hypothesis was that working in cold climate increases the risk of white fingers. METHODS: The occurrence of white fingers was investigated as a cross-sectional study in a cohort of Swedish male construction workers (N=134 757). Exposure to HAV was based on a job-exposure matrix. Living in the north or south of Sweden was, in a subgroup of the cohort, used as an indicator of the exposure to cold environment (ie, living in the north meant a higher exposure to cold climate). The analyses were adjusted for age and use of nicotine products (smoking and snuff). RESULTS: HAV-exposed workers living in a colder climate had a higher risk for white fingers than those living in a warmer climate [odds ratio (OR) 1.71, 95% confidence interval (95% CI) 1.42-2.06]. As expected, we found that HAV-exposed workers had an increased risk compared to controls (OR 2.02, 95% CI 1.75-2.34). The risk for white fingers increased with increased level of exposure to HAV and also age. CONCLUSIONS: Cold environment increases the risk for white fingers in workers occupationally exposed to HAV. The results underscore the need to keep exposure to HAV at workplaces as low as possible especially in cold climate.